NiFe-LDH surface immobilized cobalt atom modified alpha-Fe2O3 photo-anode catalyst as well as preparation method and application thereof

By solidly supporting cobalt atoms on the surface of NiFe-LDH and modifying the α-Fe2O3 photoanode, the problem of unsatisfactory performance of NiFe-LDH in catalytic water oxidation reaction is solved, and a significant improvement in catalytic water oxidation reaction performance is achieved.

CN119530862AActive Publication Date: 2025-02-28HEFEI UNIV OF TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411593267.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-02-28
Estimated Expiration
2044-11-08

AI Technical Summary

Technical Problem

In the prior art, NiFe-LDH has poor performance in catalytic water oxidation reaction, and it is difficult to effectively improve the catalytic efficiency of the α-Fe2O3 photoanode.

Method used

By solidifying cobalt atoms on the surface of NiFe-LDH, modifying the α-Fe2O3 photoanode, and preparing the catalyst by hydrothermal method, the process is simple, low cost and good repeatability.

Benefits of technology

The performance of the α-Fe2O3 photoanode modified with cobalt atoms supported on the NiFe-LDH surface is significantly improved in the catalytic water oxidation reaction, which is much higher than that of the unmodified FTO/α-Fe2O3 photoelectrode.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119530862A_ABST
    Figure CN119530862A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a NiFe-LDH surface immobilized cobalt atom modified alpha-Fe2O3 photo-anode catalyst. The preparation method comprises the following steps: putting an FTO / beta-FeOOH photo-electrode into a muffle furnace, and annealing to obtain an FTO / alpha-Fe2O3 photo-electrode; the preparation method comprises the following steps: dissolving nickel nitrate hexahydrate, ferric nitrate nonahydrate, ammonium fluoride and urea in a mixed solvent of ethylene glycol and N 'N-dimethylformamide to obtain a precursor solution; placing the FTO / alpha-Fe2O3 photoelectrode with the conductive surface upward in a hydrothermal reactor, injecting the precursor solution, and performing a reaction after sealing to obtain a NiFe-LDH modified alpha-Fe2O3 photoanode material; and adding cobalt chloride hexahydrate into a sodium borohydride solution, stirring, injecting into a hydrothermal reactor, and carrying out sealed reaction on the cobalt chloride hexahydrate and the NiFe-LDH modified alpha-Fe2O3 photo-anode material to obtain the NiFe-LDH surface immobilized cobalt atom modified alpha-Fe2O3 photo-anode catalyst. The FTO / alpha-Fe2O3 photoelectrode disclosed by the invention is subjected to high-temperature annealing to obtain a more stable crystal form; the NiFe-LDH surface immobilized cobalt atom modified alpha-Fe2O3 photo-anode catalyst is prepared by adopting a hydrothermal method, and the preparation method is simple in process, low in cost, good in repeatability, uniform in size and consistent in morphology.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of photoelectrocatalytic materials, and in particular to α-Fe modified by immobilizing cobalt atoms on the surface of NiFe-LDH. 2 O 3 Photoanode catalyst, preparation method and application. Background Art

[0002] Nowadays, the demand for efficient and high-performance catalytic systems for environmentally friendly energy is increasing. As hydrogen energy is the most promising clean and sustainable energy source, solar hydrogen production has attracted continuous attention. However, the low conversion efficiency of solar hydrogen production has greatly limited the practical application of this process. Metal oxide photoanode materials have excellent electrochemical properties, simple synthesis and low cost, making them the most attractive candidate materials for photoelectrochemical water oxidation. In particular, hematite (α-Fe 2 O 3 ) is considered to be a suitable photoanode material due to its excellent chemical stability, resistance to photocorrosion, ease of synthesis, low toxicity and abundance in nature. However, the photocatalytic efficiency of pure hematite is limited due to its fast recombination rate, low electron and hole mobility, short mean carrier path, and slow photoelectrode / electrolyte interface kinetics, which restrict its practical application. 2 O 3 Surface-supported catalyst is an important factor in improving the 2 O 3 The PEC (photoelectrocatalytic) performance is an effective method.

[0003] Two-dimensional layered double hydroxides (LDHs) have been considered as promising water oxidation decomposition (OER) materials for large-scale applications. In two-dimensional layered double hydroxides, the main active sites are edge sites, but their tightly packed basal planes severely limit the exposure of active sites. Therefore, the activation of internal functional regions is expected to improve their catalytic activity for water decomposition (Doi.org / 10.1016 / j.apcatb.2019.118559). Existing research reports show that the incorporation of a third transition metal atom, such as V, Cr, Ce, Mo, Ta, W (Doi.org / 10.1016 / j.cej.2021.130768), into NiFe-LDH can effectively regulate the electronic structure of the 3d metal matrix, further breaking the limitation of poor activity. However, the catalytic water oxidation activity of NiFe-LDH using the incorporation of transition metals is still not ideal. Summary of the invention

[0004] The technical problem to be solved by the present invention is how to provide a NiFe-LDH surface-immobilized cobalt atom-modified α-Fe 2 O 3 Photoanode catalyst and preparation method thereof.

[0005] The present invention solves the above technical problems through the following technical means:

[0006] The first aspect of the present invention provides a NiFe-LDH surface immobilized cobalt atom modified α-Fe 2 O 3 The method for preparing a photoanode catalyst comprises the following steps:

[0007] S1. The FTO / β-FeOOH photoelectrode was annealed in a muffle furnace and then treated with an ozone cleaner to obtain the FTO / α-Fe 2 O 3 Photoelectrode;

[0008] S2, dissolving nickel nitrate hexahydrate, iron nitrate nonahydrate, ammonium fluoride and urea in a mixed solvent of ethylene glycol and N'N-dimethylformamide to obtain a precursor solution;

[0009] S3. Combine FTO / α-Fe 2 O 3 The photoelectrode conductive surface is placed upward in a hydrothermal reactor, the precursor solution is injected, the reaction is carried out after sealing, and after the reaction is completed, the reaction is cooled to room temperature to obtain NiFe-LDH modified α-Fe 2 O 3 Photoanode materials;

[0010] S4, adding cobalt chloride hexahydrate to sodium borohydride solution and stirring, and injecting it into the hydrothermal reactor to react with NiFe-LDH modified α-Fe 2 O 3 The photoanode material is sealed and reacted in a thermostat. After the reaction is completed, it is cooled to room temperature to obtain α-Fe modified with cobalt atoms on the surface of NiFe-LDH. 2 O 3 Photoanode catalysts.

[0011] Beneficial effect: The photoelectrode of the present invention is annealed at high temperature to obtain a more stable FTO / α-Fe 2 O 3 Photoelectrode, and FTO / α-Fe after being treated by ozone cleaning machine 2 O 3 The surface of the photoelectrode has no other organic matter attached, so it is easier to load the catalyst. The present invention adopts a hydrothermal method to prepare α-Fe modified by immobilizing cobalt atoms on the surface of NiFe-LDH. 2 O 3The photoanode catalyst has the advantages of simple preparation process, low cost, good repeatability, uniform size and consistent morphology.

[0012] Preferably, in S1, the annealing temperature is 800° C. and the time is 2 h; the ozone cleaning machine treatment time is 0.5 h.

[0013] Preferably, in S2, the volume ratio of N'N-dimethylformamide to ethylene glycol is 1:1.

[0014] Preferably, in S2, the molar ratio of the nickel nitrate hexahydrate, the ferric nitrate nonahydrate, the ammonium fluoride and the urea is 2.5:1:1:1.

[0015] Preferably, in S3, the reaction temperature is 130-160°C and the reaction time is 16-18h.

[0016] Preferably, in S4, the pH of the sodium borohydride solution is 10-14, and the molar ratio of cobalt chloride hexahydrate to sodium borohydride in the sodium borohydride solution is 3:(1-1.5).

[0017] Preferably, in S4, the reaction temperature is 100-140° C. and the reaction time is 3-6 h.

[0018] Preferably, in S1, the preparation method of the FTO / β-FeOOH photoelectrode comprises the following steps: dissolving ferric chloride hexahydrate, sodium nitrate and concentrated hydrochloric acid in water to form a mixed solution; transferring the mixed solution and FTO to a polytetrafluoroethylene reactor, placing the polytetrafluoroethylene in a stainless steel hydrothermal reactor and sealing it for reaction; cooling to room temperature after the reaction is completed, washing and drying the obtained product to obtain the FTO / β-FeOOH photoelectrode.

[0019] The second aspect of the present invention provides a NiFe-LDH surface immobilized cobalt atom modified α-Fe 2 O 3 The photoanode catalyst is a cobalt-modified α-Fe immobilized on the surface of the NiFe-LDH. 2 O 3 The photoanode catalyst is prepared by a preparation method.

[0020] The third aspect of the present invention provides a NiFe-LDH surface immobilized cobalt atom modified α-Fe 2 O 3 Application of photoanode catalysts as photoelectrocatalysts for catalyzing water oxidation reactions.

[0021] Principle of the invention: Using the hydrothermal method, FTO / α-Fe 2 O 3 The nanoarray is used as a substrate and anionic CO3 2- NH 3 - with Ni 2+ , Fe 3+ Coordination is performed to form NiFe-LDH, and then cobalt atoms are immobilized on the surface to form NiFe-LDH. 2 O 3 The α-Fe modified by cobalt atoms was directly grown on the nano-substrate to form NiFe-LDH surface. 2 O 3 The photoanode catalyst has a consistent morphology and uniform size of the obtained product, and exhibits excellent catalytic performance in the catalytic water oxidation reaction as a photoelectrocatalyst.

[0022] The advantages of the present invention are:

[0023] The NiFe-LDH prepared by the present invention is immobilized on the surface of cobalt atoms modified α-Fe 2 O 3 The photoanode catalyst was used for photoelectrocatalytic water oxidation, showing much higher performance than FTO / α-Fe 2 O 3 Catalytic performance for photoelectrocatalytic water oxidation. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 The FTO / α-Fe obtained in Example 1 2 O 3 SEM image of the photoelectrode;

[0025] Figure 2 The α-Fe modified with cobalt atoms immobilized on the surface of NiFe-LDH obtained in Example 1 2 O 3 SEM images of the photoanode catalyst at different magnifications;

[0026] Figure 3 The α-Fe modified with cobalt atoms immobilized on the surface of NiFe-LDH obtained in Example 1 2 O 3 Photoanode catalyst (right) and FTO / α-Fe 2 O 3 Transmission electron microscopy (TEM) image of the photoelectrode (left);

[0027] Figure 4 The α-Fe modified with cobalt atoms immobilized on the surface of NiFe-LDH obtained in Example 1 2 O 3 Photoanode catalyst, NiFe-LDH catalyst and FTO / α-Fe 2 O 3X-ray photoelectron spectroscopy (XPS) of the photoelectrode; a, b, c, d and e are XPS spectra of the full spectrum, Ni, Fe, Co and O elements, respectively;

[0028] Figure 5 The α-Fe modified with cobalt atoms immobilized on the surface of NiFe-LDH obtained in Example 1 2 O 3 Surface scanning element distribution map of photoanode catalyst (Mapping); the left picture is the surface scanning element distribution area, and the right pictures ad correspond to the element distribution maps of Ni, Fe, Co, O, respectively;

[0029] Figure 6 The α-Fe modified with cobalt atoms immobilized on the surface of NiFe-LDH obtained in Example 1 2 O 3 Confocal Raman microscopy (RAMAN) of the photoanode catalyst;

[0030] Figure 7 α-Fe obtained in Comparative Example 1 2 O 3 @NiFe-LDH photoanode catalyst and α-Fe modified with cobalt atoms immobilized on the surface of NiFe-LDH obtained in Example 1 2 O 3 UV spectrum of the photoanode catalyst a and its indirect band gap spectrum calculated by UV b;

[0031] Figure 8 The α-Fe modified with cobalt atoms immobilized on the surface of NiFe-LDH obtained in Example 1 2 O 3 Photoanode catalyst and α-Fe obtained in Comparative Example 1 2 O 3 @ LSV curve of NiFe-LDH photoanode catalyst in 1M KOH solution; where α-Fe 2 O 3 Represents FTO / α-Fe 2 O 3 Photoanode catalyst, FTO / α-Fe 2 O 3 The photoanode catalyst was used as the standard catalyst;

[0032] Fig. 9 The α-Fe modified with cobalt atoms immobilized on the surface of NiFe-LDH obtained in Example 1 2 O 3 Photoanode catalyst and α-Fe obtained in Comparative Example 1 2 O 3 @IT curve of NiFe-LDH photoanode catalyst in 1M KOH solution, where α-Fe 2O 3 Represents FTO / α-Fe 2 O 3 Photoanode catalyst, FTO / α-Fe 2 O 3 The photoanode catalyst was used as the standard catalyst;

[0033] Fig.10 The α-Fe modified with cobalt atoms immobilized on the surface of NiFe-LDH obtained in Example 1 2 O 3 Photoanode catalyst and α-Fe obtained in Comparative Example 1 2 O 3 @Chopping curve of NiFe-LDH photoanode catalyst in 1M KOH solution, where α-Fe 2 O 3 Represents FTO / α-Fe 2 O 3 Photoanode catalyst, FTO / α-Fe 2 O 3 The photoanode catalyst was used as the standard catalyst;

[0034] Fig.11 The α-Fe modified with cobalt atoms immobilized on the surface of NiFe-LDH in Example 1-7 2 O 3 Schematic diagram of the preparation method of the photoanode catalyst;

[0035] Fig.12 The α-Fe modified with cobalt atoms immobilized on the surface of NiFe-LDH obtained in Example 1 2 O 3 Photoanode catalyst and α-Fe obtained in Comparative Example 1 2 O 3 @Schematic diagram of the working principle of NiFe-LDH photoanode catalyst. DETAILED DESCRIPTION

[0036] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0037] Unless otherwise specified, the test materials and reagents used in the following examples can be obtained from commercial sources.

[0038] If no specific techniques or conditions are specified in the examples, they can be carried out according to the techniques or conditions described in the literature in the art or according to the product instructions.

[0039] Example 1

[0040] Reference Fig.11 This embodiment provides a NiFe-LDH surface immobilized cobalt atom modified α-Fe 2 O 3 The method for preparing a photoanode catalyst comprises the following steps:

[0041] (1) Dissolve ferric chloride hexahydrate, sodium nitrate, and concentrated hydrochloric acid in deionized water to form a mixed solution, wherein the concentration of ferric chloride hexahydrate is 0.149 M, the concentration of sodium nitrate is 2 M, and the concentration of concentrated hydrochloric acid is 12 M. Transfer the mixed solution and FTO conductive glass to a polytetrafluoroethylene reactor, seal it with a stainless steel hydrothermal reactor, and react at 120° C. for 48 hours. After the reaction is completed, cool it to room temperature, wash and dry the obtained product to obtain a FTO / β-FeOOH photoelectrode;

[0042] (2) The FTO / β-FeOOH photoelectrode was placed in a muffle furnace and annealed at 800 °C for 2 h, and then treated with an ozone cleaner for 0.5 h to obtain the FTO / α-Fe 2 O 3 Photoelectrode;

[0043] (3) 25 mL of N,N-dimethylformamide and 25 mL of ethylene glycol were mixed uniformly, and then 0.0363 g of nickel nitrate hexahydrate, 0.0202 g of ferric nitrate nonahydrate, 0.0019 g of ammonium fluoride, and 0.0030 g of urea were added thereto, and the mixture was uniformly mixed by ultrasonic stirring to obtain a precursor solution;

[0044] (4) Combine FTO / α-Fe 2 O 3 The photoelectrode was placed in a polytetrafluoroethylene reactor with the conductive surface facing upward, and the precursor solution was slowly injected along the inner wall of the polytetrafluoroethylene reactor. After being sealed with a stainless steel hydrothermal reactor, the reaction was carried out at 160°C for 18 hours. After the reaction was completed, it was cooled to room temperature. The obtained product was washed 5 times with a mixed solution of N,N-dimethylformamide and ethanol and dried at 60°C to obtain NiFe-LDH modified α-Fe 2 O 3 Photoanode materials.

[0045] (5) 0.0214 g of cobalt chloride hexahydrate was added to a sodium borohydride solution and stirred. The sodium borohydride solution was prepared by dissolving 0.0011 g of sodium borohydride in 30 mL of deionized water. The pH of the sodium borohydride solution was 14. The stirred and mixed solution was then injected into a polytetrafluoroethylene liner to mix with the NiFe-LDH-modified α-Fe 2 O 3 The photoanode materials were mixed, sealed and placed in a 120°C oven for reaction for 3 h. After the reaction was completed, the mixture was cooled to room temperature to obtain α-Fe modified with cobalt atoms on the surface of NiFe-LDH. 2 O 3 Photoanode catalysts.

[0046] Depend on Figure 1-2 It can be seen that the surface of NiFe-LDH obtained in this example is immobilized with cobalt atoms modified α-Fe 2 O 3 The photoanode catalyst is heterogeneous and of uniform size; Figure 3 and 5 It can be seen that the surface of NiFe-LDH obtained in this example is immobilized with cobalt atoms modified α-Fe 2 O 3 Photoanode catalyst, successfully on FTO / α-Fe 2 O 3 The photoelectrode was loaded with NiFe-LDH and cobalt atoms were successfully immobilized on the surface.

[0047] Figure 4 This reflects the immobilization of cobalt atoms on the surface of NiFe-LDH to modify α-Fe 2 O 3 Element composition and valence state of the photoanode catalyst surface; a is the full spectrum, showing the presence and content of elements such as Ni, Fe, Co, and O, where the intensity of the peak indicates their relative content. b, c, d, and e are the spectra of Ni, Fe, Co, and O, respectively, revealing the valence state of these elements and their bonding types. As shown in Figure a, the α-Fe modified with cobalt atoms immobilized on the surface of NiFe-LDH 2 O 3 The presence of Co element in the photoanode catalyst and the detection of Co atoms with corresponding valence states in Figure d indicate that Co atoms were successfully immobilized on the NiFe-LDH surface.

[0048] from Figure 6 Typical NiFe-LDH peaks can be seen at 447 nm and 532 nm, and the overall peak shifts, indicating that the cobalt-modified α-Fe 2 O 3 The photoanode catalyst was successfully prepared.

[0049] Comparative Example 1

[0050] This comparative example provides an α-Fe 2 O 3 The specific steps of the preparation method of @NiFe-LDH photoanode catalyst are as follows:

[0051] (1) Dissolve ferric chloride hexahydrate, sodium nitrate, and concentrated hydrochloric acid in deionized water to form a mixed solution, wherein the concentration of ferric chloride hexahydrate is 0.149 M, the concentration of sodium nitrate is 2 M, and the concentration of concentrated hydrochloric acid is 12 M. Transfer the mixed solution and FTO conductive glass to a polytetrafluoroethylene reactor, seal it with a stainless steel hydrothermal reactor, and react at 120° C. for 48 hours. After the reaction is completed, cool it to room temperature, wash and dry the obtained product to obtain a FTO / β-FeOOH photoelectrode;

[0052] (2) The FTO / β-FeOOH photoelectrode was placed in a muffle furnace and annealed at 800 °C for 2 h, and then treated with an ozone cleaner for 0.5 h to obtain the FTO / α-Fe 2 O 3 Photoelectrode;

[0053] (3) 25 mL of N,N-dimethylformamide and 25 mL of ethylene glycol were mixed uniformly, and then 0.0363 g of nickel nitrate hexahydrate, 0.0202 g of ferric nitrate nonahydrate, 0.0019 g of ammonium fluoride, and 0.0030 g of urea were added thereto, and the mixture was stirred and ultrasonically mixed to obtain a precursor solution;

[0054] (4) Combine FTO / α-Fe 2 O 3 The photoelectrode conductive surface was placed upward in a polytetrafluoroethylene reactor, and the precursor solution was slowly injected along the inner wall of the polytetrafluoroethylene reactor. After being sealed with a stainless steel hydrothermal reactor, the reaction was carried out at 160°C for 18 hours. After the reaction was completed, it was cooled to room temperature. The obtained product was washed 5 times with a mixed solution of N,N-dimethylformamide and ethanol and dried at 60°C to obtain α-Fe 2 O 3 @NiFe-LDH photoanode catalyst.

[0055] from Figure 7 It can be seen that the surface of NiFe-LDH obtained in Example 1 is immobilized with cobalt atoms modified with α-Fe 2 O 3 The indirect band gap of the photoanode catalyst is larger than that of the α-Fe 2 O 3 @NiFe LDH photoanode catalyst and FTO / α-Fe 2 O 3 The photoelectrode has a smaller band gap, which is more conducive to absorbing light for water oxidation reaction.

[0056] Depend on Figure 8 It can be seen that the surface of NiFe-LDH obtained in Example 1 is immobilized with cobalt atoms modified with α-Fe 2 O 3 The photocurrent density of the photoanode catalyst reached 0.727 mA cm at a bias voltage of 1.23 VRHE. -2 , compared with FTO / α-Fe 2 O 3 The photoelectrode is 0.159 mA cm -2 The photocurrent density of the α-Fe 2 O 3 @NiFe LDH photoanode catalyst at 1.23V RHE The photocurrent density under bias voltage reaches 0.412 mA cm -2 Compared with the α-Fe modified with cobalt atoms immobilized on the surface of NiFe-LDH obtained in Example 1, 2 O 3 The photocurrent density of the photoanode catalyst was significantly reduced.

[0057] Depend on Fig. 9 It can be seen that the surface of the NiFe LDH obtained in Example 1 is immobilized with cobalt atoms modified with α-Fe 2 O 3 The photocurrent density of the photoanode catalyst did not decay significantly within 10 min under 1.23 VRHE bias. 2 O 3 @The photocurrent density of the NiFe LDH photoanode catalyst showed a significant decay within 10 minutes under a bias of 1.23VRHE.

[0058] Depend on Fig.10 It can be seen that the surface of NiFe-LDH obtained in Example 1 is immobilized with cobalt atoms modified with α-Fe 2 O 3 Compared with FTO / α-Fe 2 O 3 Photoelectrode and α-Fe obtained in Comparative Example 1 2 O 3 @NiFe-LDH photoanode catalyst is more sensitive to light.

[0059] Depend on Fig.12 It can be seen that the α-Fe 2 O 3 When NiFe-LDH photoanode catalyst oxidizes water, the electron transfer rate is slow and the hole recombination rate is slightly high. However, the α-Fe modified with cobalt atoms is immobilized on the surface of NiFe-LDH obtained in Example 1. 2 O 3When the photoanode catalyst oxidizes water, the cobalt atoms promote the rapid transfer of electrons, greatly reducing the hole recombination rate and promoting the oxygen evolution reaction kinetics more significantly.

[0060] Example 2

[0061] This embodiment provides a NiFe-LDH surface immobilized cobalt atom modified α-Fe 2 O 3 The steps of the preparation method of the photoanode catalyst are different from those of Example 1 only in that: in step (4), the reaction temperature is 130° C. and the reaction time is 16 h; the remaining steps are the same as those of Example 1.

[0062] The results show that the NiFe-LDH surface is immobilized with cobalt atoms modified with α-Fe 2 O 3 The photoanode catalysts are heterogeneous in structure and have uniform size.

[0063] The same method as in Example 1 was used to test the NiFe LDH obtained in this example. The surface of the NiFe LDH was immobilized with cobalt atoms modified with α-Fe 2 O 3 The photocurrent density of the photoanode catalyst reached 0.691 mA cm at a bias voltage of 1.23 VRHE. -2 , there is no obvious decay of photocurrent density within 10 minutes.

[0064] Example 3

[0065] This embodiment provides a NiFe-LDH surface immobilized cobalt atom modified α-Fe 2 O 3 The steps of the preparation method of the photoanode catalyst are different from those of Example 1 only in that: in step (5), the reaction temperature is 100° C. and the reaction time is 4 h; the remaining steps are the same as those of Example 1.

[0066] The results show that the NiFe-LDH surface is immobilized with cobalt atoms modified with α-Fe 2 O 3 The photoanode catalysts are heterogeneous in structure and have uniform size.

[0067] The same method as in Example 1 was used to test the NiFe-LDH surface obtained in this example. 2 O 3 The photocurrent density of the photoanode catalyst reached 0.684 mA cm at a bias voltage of 1.23 VRHE. -2 , there is no obvious decay of photocurrent density within 10 minutes.

[0068] Example 4

[0069] This embodiment provides a NiFe-LDH surface immobilized cobalt atom modified α-Fe 2 O 3 The steps of the preparation method of the photoanode catalyst are different from those of Example 1 only in that: in step (5), the reaction temperature is 140° C. and the reaction time is 5 h; the remaining steps are the same as those of Example 1.

[0070] The results show that the NiFe-LDH surface is immobilized with cobalt atoms modified with α-Fe 2 O 3 The photoanode catalysts are heterogeneous in structure and have uniform size.

[0071] The same method as in Example 1 was used to test the NiFe-LDH surface obtained in this example. 2 O 3 The photocurrent density of the photoanode catalyst reached 0.688 mA cm at a bias voltage of 1.23 VRHE. -2 , there is no obvious decay of photocurrent density within 10 minutes.

[0072] Example 5

[0073] This embodiment provides a NiFe-LDH surface immobilized cobalt atom modified α-Fe 2 O 3 The steps of the method for preparing the photoanode catalyst are different from those of Example 1 only in that: in step (4), the pH value of the sodium borohydride solution is 10; the remaining steps are the same as those of Example 1.

[0074] The results show that the NiFe-LDH surface is immobilized with cobalt atoms modified with α-Fe 2 O 3 The photoanode catalysts are heterogeneous in structure and have uniform size.

[0075] The same method as in Example 1 was used to test the NiFe-LDH surface obtained in this example. 2 O 3 The photocurrent density of the photoanode catalyst reached 0.701 mA cm at a bias voltage of 1.23 VRHE. -2 , there is no obvious decay of photocurrent density within 10 minutes.

[0076] Example 6

[0077] This embodiment provides a NiFe-LDH surface immobilized cobalt atom modified α-Fe 2 O 3The steps of the method for preparing the photoanode catalyst are different from those of Example 1 only in that: in step (4) and in step (5), the reaction temperature is 140° C. and the reaction time is 3 h; the remaining steps are the same as those of Example 1.

[0078] The results show that the NiFe-LDH surface is immobilized with cobalt atoms modified with α-Fe 2 O 3 The photoanode catalysts are heterogeneous in structure and have uniform size.

[0079] The same method as in Example 1 was used to test the NiFe-LDH surface obtained in this example. 2 O 3 The photocurrent density of the photoanode catalyst reached 0.665 mA cm at a bias voltage of 1.23 VRHE. -2 , there is no obvious decay of photocurrent density within 10 minutes.

[0080] Example 7

[0081] This embodiment provides a NiFe-LDH surface immobilized cobalt atom modified α-Fe 2 O 3 The steps of the method for preparing the photoanode catalyst are different from those of Example 1 only in that: in step (4) and in step (5), the mass of sodium borohydride in the sodium borohydride solution is 0.0022 g; the remaining steps are the same as those of Example 1.

[0082] The results show that the NiFe-LDH surface is immobilized with cobalt atoms modified with α-Fe 2 O 3 The photoanode catalysts are heterogeneous in structure and have uniform size.

[0083] The same method as in Example 1 was used to test the NiFe-LDH surface obtained in this example. 2 O 3 The photocurrent density of the photoanode catalyst reached 0.698 mA cm at a bias voltage of 1.23 VRHE. -2 , there is no obvious decay of photocurrent density within 10 minutes.

[0084] Comparative Example 2

[0085] In Comparative Example 2, the NiFe-LDH surface was immobilized with cobalt atoms modified with α-Fe 2 O 3 The preparation method of the photoanode catalyst is similar to that of Example 1, except that the reaction temperature in step (5) is 80°C.

[0086] The same method as in Example 1 was used to test the surface of the NiFe-LDH obtained in Comparative Example 2. 2 O 3 The photoanode catalyst has a photocurrent density of 0.354 mA cm at a bias voltage of 1.23 VRHE. -2 Compared with the α-Fe modified with cobalt atoms immobilized on the surface of NiFe LDH in Example 1, 2 O 3 The photocurrent density of the photoanode catalyst decreased, and the photocurrent density declined significantly within 10 minutes.

[0087] Comparative Example 3

[0088] The preparation method of the α-Fe2O3 photoanode catalyst modified with cobalt atoms immobilized on the surface of NiFe LDH in Comparative Example 3 is similar to that in Example 1, except that the reaction temperature in step (4) is 200°C.

[0089] The same method as in Example 1 was used to test the surface of the NiFe-LDH prepared in this comparative example 3. 2 O 3 The photocurrent density of the photoanode catalyst reached 0.378 mA cm at a bias voltage of 1.23 VRHE. -2 Compared with the α-Fe modified with cobalt atoms immobilized on the surface of NiFe LDH in Example 1, 2 O 3 The photocurrent density of the photoanode catalyst decreased, and the photocurrent density declined significantly within 10 minutes.

[0090] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a NiFe-LDH surface-immobilized cobalt atom-modified α-Fe2O3 photoanode catalyst, characterized in that: The following steps are involved: S1, placing the FTO / β-FeOOH photoelectrode in a muffle furnace for annealing, and then treating it with an ozone cleaner to obtain a FTO / α-Fe2O3 photoelectrode; S2, dissolving nickel nitrate hexahydrate, iron nitrate nonahydrate, ammonium fluoride and urea in a mixed solvent of ethylene glycol and N,N-dimethylformamide to obtain a precursor solution; S3, placing the FTO / α-Fe2O3 photoelectrode with the conductive surface facing upward in a hydrothermal reactor, injecting the precursor solution, sealing it and reacting it, and cooling it to room temperature after the reaction to obtain the NiFe-LDH modified α-Fe2O3 photoanode material; S4. Add cobalt chloride hexahydrate into sodium borohydride solution and stir, and inject it into a hydrothermal reactor to react with NiFe-LDH modified α-Fe2O3 photoanode material in a sealed manner. The reaction is carried out in an incubator. After the reaction is completed, it is cooled to room temperature to obtain α-Fe2O3 photoanode catalyst modified with cobalt atoms immobilized on the surface of NiFe-LDH.

2. The method for preparing the α-Fe2O3 photoanode catalyst modified with cobalt atoms immobilized on the surface of NiFe-LDH according to claim 1, characterized in that: In S1, the annealing temperature is 800° C. and the time is 2 hours; the ozone cleaning machine treatment time is 0.5 hours.

3. The method for preparing the α-Fe2O3 photoanode catalyst modified with cobalt atoms immobilized on the surface of NiFe-LDH according to claim 1, characterized in that: In S2, the volume ratio of N,N-dimethylformamide to ethylene glycol is 1:

1.

4. The method for preparing the α-Fe2O3 photoanode catalyst modified with cobalt atoms immobilized on the surface of NiFe-LDH according to claim 1, characterized in that: In S2, the molar ratio of the nickel nitrate hexahydrate, the ferric nitrate nonahydrate, the ammonium fluoride and the urea is 2.5:1:1:

1.

5. The method for preparing the α-Fe2O3 photoanode catalyst modified with cobalt atoms immobilized on the surface of NiFe-LDH according to claim 1, characterized in that: In S3, the reaction temperature is 130-160°C and the reaction time is 16-18h.

6. The method for preparing the α-Fe2O3 photoanode catalyst modified with cobalt atoms immobilized on the surface of NiFe-LDH according to claim 1, characterized in that: In S4, the pH of the sodium borohydride solution is 10-14, and the molar ratio of cobalt chloride hexahydrate to sodium borohydride in the sodium borohydride solution is 3:(1-1.5).

7. The method for preparing the α-Fe2O3 photoanode catalyst modified with cobalt atoms immobilized on the surface of NiFe-LDH according to claim 1, characterized in that: In S4, the reaction temperature is 100-140°C and the reaction time is 3-6h.

8. The method for preparing the α-Fe2O3 photoanode catalyst modified with cobalt atoms immobilized on the surface of NiFe-LDH according to any one of claims 1 to 7, characterized in that: In S1, the preparation method of the FTO / β-FeOOH photoelectrode includes the following steps: dissolving ferric chloride hexahydrate, sodium nitrate and concentrated hydrochloric acid in water to form a mixed solution; transferring the mixed solution and FTO to a polytetrafluoroethylene reactor, placing the polytetrafluoroethylene in a stainless steel hydrothermal reactor and sealing it for reaction; cooling to room temperature after the reaction is completed, washing and drying the obtained product to obtain the FTO / β-FeOOH photoelectrode.

9. An α-Fe2O3 photoanode catalyst modified with cobalt atoms immobilized on the surface of NiFe-LDH, characterized in that: The catalyst is prepared by the method for preparing an α-Fe2O3 photoanode catalyst modified with cobalt atoms immobilized on the surface of NiFe-LDH as described in any one of claims 1 to 8.

10. Use of the α-Fe2O3 photoanode catalyst modified with cobalt atoms immobilized on the surface of NiFe-LDH as claimed in claim 9 as a photoelectrocatalyst for catalyzing water oxidation reaction.

Citation Information

Patent Citations

  • NiCoAl-LDH-modified ferric oxide composite photoanode material and preparation method and application thereof

    CN107268021A

  • Co (OH) 2 modified NiAl-LDH / alpha-Fe2O3 composite photo-anode and preparation method thereof

    CN114438515A

  • P-n heterojunction composite material supported on surface of nickel foam, preparation method therefor and application thereof

    US20220355286A1